Regulation of the water-salt regime of irrigated lands in the lowerof the Syrdarya River (Journal of Geography and Environmental Management, 2021)
In general, the salinity of the water of the Syrdarya river, the current soil-reclamation state of the irrigated lands located in the lower reaches of the Syrdarya river are very poor. Soil salinity and salinity of collector-drainage waters are very high. For example, the average annual salinity of river water at the Tomenaryk gauging station is 2.0-2.5 g / l, and at the Kazalinsky gauging station - 3.0-3.5 g / l. Moreover, the process of soil salinization took place practically throughout the entire territory of the region. For example, according to the latest data, the area of ​​saline irrigated land in the Kyzylorda region is about 225 940 hectares, of which slightly saline - 87 574 hectares, moderately saline - 73 302 hectares, strongly and very strongly saline - 65 064 hectares. The Kyzylorda region is mainly engaged in the cultivation of rice (as well as alfalfa, corn for silage, sunflower, etc.). Considering this, secondary salinization was observed in rice fields due to poor performance of collector-drainage systems. After all, all of this is known to have a negative impact on crop yields. Therefore, we can get the best results only with the right watering with the right measures and capabilities.To optimize this issue, the article presents the current state of irrigated lands in the lower reaches of the Syrdarya river in the Kyzylorda region, as well as the results of work on regulating the water-salt regime. For this purpose, research work was carried out on 71.15 hectares of agricultural land Bidaikol (formerly Gigant), belonging to the Zhanakorgan-Shieli irrigation massif. It provides for the analysis of the amount of salts entering the soil with irrigation water and the release of salts from the soil by collector-drainage waters, measures to improve the ecological-reclamation state of the soil. And also the positive results of studies carried out on the site to improve the water-salt regime of the soil are presented.According to the research results, it was optimal to provide the fields with water through a specially prepared biofield planted with dense reed plants. It has been proven that purified irrigation water from the biofield is effective for irrigating forage crops. In addition, the reed itself is widely used in the republic as a fodder crop. Young reeds collected in August (at this time the reeds will be soft, and the leaves are green) are finely chopped and stored using a press using a special technology. Due to the growing importance of winter forage, the price of cane has increased significantly in the southern and southwestern regions of the country. For example, this year the price of 1 cane press fluctuated within 650-850 tenge. In addition, this spring there was a shortage of feed in the western regions (Aktau, Mangistau). Considering all these problems, the technology of water supply for irrigation through the biofield is more efficient.
Keywords: salinization; experimental field; irrigated lands; checks; leaching; water-salt regime; collectors and drainages